The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1073/pnas.95.7.3857
|View full text |Cite
|
Sign up to set email alerts
|

C-C chemokines, pivotal in protection against HIV type 1 infection

Abstract: Exposure to HIV type 1 (HIV-1) does not usually lead to infection. Although this could be because of insufficient virus titer, there is now abundant evidence that some individuals resist infection even when directly exposed to a high titer of HIV. This protection recently has been correlated with homozygous mutations of an HIV-1 coreceptor, namely CCR5, the receptor for the ␤-chemokines. Moreover, earlier results already had shown that the same chemokines markedly suppress the nonsyncitial inducing variants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(145 citation statements)
references
References 30 publications
7
135
0
Order By: Relevance
“…Because β-chemokines may block HIV propagation in vitro [29,30] and heightened β-chemokine expression also has been seen in high-risk HIV-seronegative persons [31,32], we wanted to assess the relationship between β-chemokine production and genetic regulation of CCR5 expression. For these studies, we assayed cell culture supernatants for MIP-1α, MIP-1β, and RANTES by ELISA (R&D Systems, Minneapolis, MN, USA) after 48 h of cultivation without stimulation or after stimulation with PHA and IL-2 at suboptimal, nearoptimal, and optimal stimulation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Because β-chemokines may block HIV propagation in vitro [29,30] and heightened β-chemokine expression also has been seen in high-risk HIV-seronegative persons [31,32], we wanted to assess the relationship between β-chemokine production and genetic regulation of CCR5 expression. For these studies, we assayed cell culture supernatants for MIP-1α, MIP-1β, and RANTES by ELISA (R&D Systems, Minneapolis, MN, USA) after 48 h of cultivation without stimulation or after stimulation with PHA and IL-2 at suboptimal, nearoptimal, and optimal stimulation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that increased production of RANTES, MIP-1␣, and MIP-1␤ correlates with resistance to infection or a more favorable clinical prognosis, likely because of competition of the chemokines with HIV-1 for binding to CCR5 (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Several reports have suggested an association between exposed uninfected individuals and high levels of endogenous CC chemokines (macrophage inflammatory protein 1a and 1ß, MIP-1a and MIP-1ß) and RANTES (regulated-upon-activation, normal T expressed and secreted), suggesting that a chemokine may contribute to clinical resistance in some cases (4,5). Because the ß-chemokines are major components of the HIV-1 suppressive soluble factor extensively studied nowadays (6)(7)(8)(9)(10)(11)(12), the present study was undertaken to determine the relationship between plasma concentrations of MIP1a and RANTES and viral load in Brazilian HIV-1-infected subjects.…”
mentioning
confidence: 99%
“…The reason for this difference is not known, although it may be due to variations among the individuals studied. One possible explanation for the lower MIP-1a plasma concentrations could be that the HIV-1 Tat protein may cause downregulation of mRNA and suppress the secretion of MIP-1a and MIP-1ß (5,18). In a recent study, MIP-1a was shown to have a 10-fold higher affinity than RANTES for CCR5 (19).…”
mentioning
confidence: 99%